Factors Associated with Mobilisation in Post-Operative Lapatomy Patients at Urip Sumoharjo Hospital Bandar Lampung in 2025 - Sri Wahyuni Iman; Surmasih; Chusairil Pasa (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2026)
Background & Objective: The World Health Organisation (WHO) recorded 98 million laparotomy cases in 2022, while Lampung Province had the seventh highest number of laparotomy cases in 2020, accounting for approximately 21.7% of the total number of operations. Urip Sumoharjo Hospital (2024) recorded 3,307 surgical procedures performed throughout 2024, with 630 of them being laparotomy surgeries. However, approximately 35% of post-operative patients did not undergo early mobilisation. This study aims to determine the factors associated with mobilisation in post-laparotomy patients at Urip Sumoharjo Hospital in Bandar Lampung in 2025. Method: The type of research was quantitative with a quantitative design using a cross-sectional approach. Total sampling was used, resulting in 50 respondents. The research was conducted at Urip Sumoharjo Hospital for one month from 2 October to 2 November. The collected data were analysed statistically using the gamma test to examine the relationship between variables. Result: The results of the study indicate a significant relationship between family support, knowledge, motivation (p-value <0.001 (< 0.05) and mobilisation implementation. Conclusion: It can therefore be concluded that family support, knowledge and motivation play an important role in the successful mobilisation of patients. Patients are expected to broaden their understanding of the benefits of mobilisation and maintain high self-motivation in order to routinely increase the frequency of independent movement. In addition, active family involvement is essential as the main support in accompanying patients through the stages recommended by health workers to achieve optimal physical recovery.